Reviews : Can a machine think?. (1st April 2020) - Curtis, Susan
Abstract: Artificial intelligence is a research field that attracts its fair share of hyperbole. Michael Wooldridge, a professor of AI at the University of Cambridge, seeks to rewrite that mainstream narrative in his latest book The Road to Conscious Machines: the Story of AI .